The Role of Cellular Senescence During Vascular Calcification: A Key Paradigm in Aging Research - Mackenzie, N. C.W.; E. MacRae, V. (Current Aging Science, 2011)
Vascular calcification has severe clinical consequences and is considered an accurate predictor of future adverse cardiovascular events. Vascular calcification refers to the deposition of calcium phosphate mineral, most often hydroxyapatite, in arteries. Extensive calcification of the vascular system is a key characteristic of aging. In this article, we outline the mechanisms governing vascular calcification and highlight its association with cellular senescence. This review discusses the molecular mechanisms of cellular senescence and its affect on calcification of vascular cells, the relevance of phosphate regulation and the function of FGF23 and Klotho proteins. The association of vascular calcification and cellular senescence with the rare human aging disorder Hutchison-Gilford Progeria Syndrome (HGPS) is highlighted and the mouse models used to try to determine the underlying pathways are discussed. By understanding the pathways involved in these processes novel drug targets may be elucidated in an effort to reduce the effects of cellular aging as a risk factor in cardiovascular disease.
Keywords: Vascular disease